Congenital diaphragmatic hernia associated with esophageal atresia, tracheoesophageal fistula and total anomalous pulmonary venous connection in a premature twin newborn - Savic, Djordje Milan; Grujić, Blagoje; Stanković, Nikola; Miličković, Maja; Stanković, Zoran; Kojović, Vladimir (Vojnosanitetski pregled, 2021)
Abstract Introduction. Congenital diaphragmatic hernia (CDH) with concomitant esophageal atresia (EA) and tracheo-esophageal fistula (TEF) is a very rare condition, with a high mortality rate. Prematurity and congenital heart anomalies additionally increase the mortality rate. This situation is a great challenge for clinicians, requiring multidisciplinary work and adequate treatment strategy. Case report. We presented a premature twin newborn at the gestational age of 33/34 weeks with body mass of 1690 g. The existence of the left CDH was established on prenatal ultrasound exam in the 24th gestational week, and the diagnosis of EA with TEF was made on admittance to our hospital. The cardiac ultrasound exam revealed the total anomalous pulmonary venous connection (TAPVC). The first operation was performed on the day of admittance and consisted of left subcostal laparotomy, diaphragmatic repair, elastic occlusion of the gastroesophageal junction and gastrostomy. The ligation of TEF and esophagoplasty were done 13 days later in the second operation. The lethal outcome during the esophagoplasty was caused by the crisis of pulmonary hypertension and associated congenital heart anomaly (TAPVC). The presence of CDH and EA/TEF in association with TAPVC in a twin newborn has not been reported before in the literature. Conclusion. The treatment of newborns with CDH and EA/TEF requires multidisciplinary well-coordinated team work of pediatric surgeons, anaesthesiologists, neonatologists and pulmologists. The standard protocol for the management does not exist, but well-planned staged operations could enable greater survival rate.
Keywords: infant, premature; congenital abnormalities; hernia, diaphragmatic; esophageal atresia; tracheoesophageal fistula; heart defects, congenital; digestive system surgical procedures